Association Between Antihypertensive Medication Use and Breast Cancer: A Systematic Review and Meta-Analysis - Xie, Yuxiu; Wang, Men; Xu, Peng; Deng, Yujiao; Zheng, Yi; Yang, Si; Wu, Ying; Zhai, Zhen; Zhang, Dai; Li, Na; Wang, Nan; Cheng, Jing; et al. (Frontiers in Pharmacology, 2021)
Background: The prevalence rate of hypertension and breast cancer increases with advancing age. Renin-angiotensin system inhibitors (RASIs), β-blockers (BBs), calcium channel blockers (CCBs), and diuretics are widely used to treat patients with hypertension. Although, the association between the use of antihypertensive medication and breast cancer has been highly debated, recent evidence supporting this association remains controversial. Objective: To evaluate the association between the use of antihypertensive medication and the risk of breast cancer and its prognosis. Methods: This study was conducted using data from the PubMed, Embase, and Cochrane Library databases retrieved for the period from January 2000 to June 2020. Articles and their references were checked and summary effects were calculated using random- and fixed-effects models. Heterogeneity test and sensitivity analysis were also performed. Results: This meta-analysis included 56 articles, which were all related to breast cancer risk or prognosis. Assessment of breast cancer risk using the pooled data showed that the use of BBs or CCBs or diuretics was associated with increased cancer risk (BB: relative risk [RR] = 1.07, 95% confidence interval [CI] = 1.04-1.10; CCBs: RR = 1.06, 95% CI = 1.03-1.08; diuretics: RR=1.06, 95% CI = 1.01-1.11). Long-term use of diuretic increased the risk of breast cancer (RR = 1.10, 95% CI = 1.01-1.20), whereas long-term RASIs treatment reduced the risk (RR = 0.78, 95% CI = 0.68-0.91). In addition, we found that diuretic users may be related to elevated breast cancer-specific mortality (hazard ratio [HR] = 1.18, 95% CI = 1.04-1.33), whereas using other antihypertensive medications was not associated with this prognosis in patients with breast cancer. Conclusions: Using CCBs, BBs, and diuretics increased the risk of breast cancer. In addition, diuretics may elevate the risk of breast cancer-specific mortality. The long-term use of RASIs was associated with a significantly lower breast cancer risk, compared with non-users. Thus, this analysis provides evidence to support the benefits of the routine use of RASIs in patients with hypertension, which has important public health implications.